Transcendence through Rhetorical Practices: Responding to Paradox in the Science Sector - Bednarek, Rebecca; Paroutis, Sotirios; Sillince, John (Organization studies, 2017)
Organizations are often required to meet contradictory but interrelated objectives. An important response to such paradoxes is transcendence: the ability to view both poles of the paradox as necessary and complementary. Despite the centrality of transcendence to existing frameworks within the paradox literature, we still know little about its practice. We address this gap by surfacing and analysing rhetorical practices across three science organizations. We outline four rhetorical practices that constitute transcendence (Ordering, Aspiring, Signifying, and Embodying) as well as the underlying features of these practices that explain how they construct a response to paradox. In particular, we show that transcendence entailed balancing the enabling features of focus (paradoxical content/context), time (stability/change) and distance (maintaining/reducing). Finally, we develop a dynamic view of transcendence as a process of oscillation, showing how these practices are bundled together and interrelate to construct moments of transcendence.